THE EFFECT OF THE PHYSICOCHEMICAL PROPERTIES OF A DRUG ON ITS RELEASE FROM CHITOSONIUM MALATE MATRIX TABLETS - (:unkn) unknown (ELSEVIER SCIENCE BV, 1993)
The effect of the physico-chemical properties of an active compound (such as solubility and molecular size) on its release characteristics from chitosonium malate matrix tablets has been investigated. For this purpose, the release of 11 drugs of various solubilities (1 in < 1 to 1 in 10000) and molecular weights (138-375) through chitosonium malate matrix tablets was studied. It may be concluded that, in addition to the solubility, the molecular size of drug is of importance in the drug release characteristics from the chitosonium malate matrix. When the release data (< 60%) were fitted to the simple power law equation, the mode of drug release from the chitosonium malate matrix was generally non-Fickian and Super Case II type. These drugs (timolol maleate, ephedrine, propranolol hydrochloride, acetylsalicylic acid, naproxen, sulphadiazine, indomethacin and pindolol) can be released at a nearly zero-order rate through the matrix.
Keywords: CHITOSAN; CHITOSONIUM MALATE; MATRIX TABLET; SWELLING CONTROL; SUSTAINED RELEASE; DRUG SOLUBILITY; MOLECULAR SIZE; RELEASE MECHANISM; CHITOSAN; SOLUTE